Analysis of Clay Silt Reserve Using Geoelectricity in the Village of Dulohupa District of Gorontalo - Dewa Gede Eka Setiawan; Abd. Wahidin Nuayi (Politeknik Negeri Batam, 2017)
This research aims to investigate clay silt reserve in brick farmer area. This research applies geoelectricity by using Schlumberger configuration conducted by doing injection of electric current with low frequency to surface of earth. Value of resistance will bring information about structure and materials across by it.Research site is in four stations and based on the geographical location in the station I at coordinate N 00 ° 35'43.7